TAʿLĪM AL-LUĠAH AL-ʿARABIYYAH FĪ AL-MAʿĀHID AL-ISLĀMIYYAH FĪ INDŪNĪSIYYĀ - Noor Sa'adah (Jurnal Al-Maqoyis, 2020)
This study aims to describe the academic material in Arabic teaching in the salaf and the modern Institutions, and describe the similarities and differences of Arabic teaching in both of them.The study  used  a qualitative.  In this  study  the  data  were  collected  by  using  interviews, observation, and documentation. To analyze  the  data,  the  researcher  used  the  interactive  technique  of  Miles  and Huberman,  while  to  test the  validity  of  the  data,  the  method  of  triangulation  technique  was  used.The result of the study shows the following: (1) The Arabic teaching materials in Rasyidiyah Khalidiyah Islamic boarding schools consist of 10 subjects, while in the Raudhatut Thalibin only consist of 5 subjects. The Rasyidiyah Khalidiyah boarding schools use theory of integrated and separated system in their Arabic teaching materials, while the Raudhatut Thalibin use separated system theory; (2) The instructional method engaged in Arabic teaching is the eclectic method. The teaching use concrete (indrawi) media. Both oral and written test were applied in the evaluation system; (3) The kinds of language environment applied in Arabic teaching in Rasyidiyah Kalidiyah Islamic boarding school consist of the environment of listening and reading. While speaking, reading and listening environments, were applied in Raudhatut Thalibin Islamic boarding school.Keywor